APPLICATION OF KUNIRAN FISH PROTEIN ISOLATE (Upeneus sulphureus) AS AN EMULSIFIER IN CHICKEN SAUSAGE - Detia Setiani; Sakinah Haryati; Bhatara Ayi Meata (Jurnal Gizi dan Pangan Soedirman, 2026)
Chicken sausage is a processed food product made from meat. A common problem in sausage making is the emulsion breaking during the processing process, resulting in an unstable texture. Therefore, an emulsifier is needed to maintain emulsion stability. This study aims to determine the optimum concentration of fish protein isolate as an emulsifier in chicken sausage. The method used was a completely randomized design with the addition of kuniran fish (Upeneus sulphureus) protein isolate at concentrations of 0%, 2.5%, 5%, and 7.5% with 3 replications for each treatment. Data on cooking loss, water-holding capacity, moisture content, ash, protein, and fat were analyzed using one-way ANOVA at a 5% level and continued with DMRT. Organoleptic tests were analyzed using Kruskal-Wallis and Mann-Whitney. The results showed that kuniran fish protein isolate used as an emulsifier in chicken sausage at a concentration of 7.5% (treatment P3) was optimal as an emulsifier in chicken sausage. The ANOVA test showed a cooking loss value of 8.33%, water holding capacity of 62.51%, water content of 28.74%, ash content of 6.26%, protein content of 51.60%, and fat content of 13.22%. The organoleptic test of P3 obtained good acceptance in all parameters. The Total Plate Count (TPC) value of the microbiological test was 3.2x10³ CFU/g, meeting SNI requirements.